2016
DOI: 10.3233/jad-160491
|View full text |Cite
|
Sign up to set email alerts
|

Amyloid-β Increases Activity of Proteasomes Capped with 19S and 11S Regulators

Abstract: Accumulation of amyloid-β (Aβ) in neurons accompanies Alzheimer's disease progression. In the cytoplasm Aβ influences activity of proteasomes, the multisubunit protein complexes that hydrolyze the majority of intracellular proteins. However, the manner in which Aβ affects the proteolytic activity of proteasomes has not been established. In this study the effect of Aβ42 and Aβ42 with isomerized Asp7 on activity of different forms of proteasomes has been analyzed. It has been shown that Aβ peptides efficiently r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…2bd). These data are also in line with our and previous findings by others where decrease of the pure 20S proteasome activity following incubation with different Aβ peptides was demonstrated (Morozov 2016;Tseng et al 2008;Zhao and Yang 2010). However, Zhao and Yang have shown that Aβ is a substrate of 20S proteasome and observed proteasome inhibition results from protein and fluorogenic peptide competition for the active sites of the proteasome (Zhao and Yang 2010).…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…2bd). These data are also in line with our and previous findings by others where decrease of the pure 20S proteasome activity following incubation with different Aβ peptides was demonstrated (Morozov 2016;Tseng et al 2008;Zhao and Yang 2010). However, Zhao and Yang have shown that Aβ is a substrate of 20S proteasome and observed proteasome inhibition results from protein and fluorogenic peptide competition for the active sites of the proteasome (Zhao and Yang 2010).…”
Section: Discussionsupporting
confidence: 93%
“…On the other hand, the 20S fraction contains large amount of proteasomes with 11S regulators ( Fig. 3g) (Morozov 2016), which represent the most catalytically active form of proteasome in this fraction (Morozov 2016). Keeping in mind very low amount of 26S proteasomes in the 20S fraction (Fig.…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations